Factors influencing hygienic behavior among students in Central Kazakhstan during COVID-19 - Bolatova, Zhanerke; Kalishev, Marat; Nukeshtayeva, Karina; Zhamantayev, Olzhas; Dauletkaliyeva, Zhaniya; Kayupova, Gaukhar; Yerdessov, Nurbek; Orru, Hans (Frontiers in Public Health, 2025)
IntroductionHand hygiene is a fundamental public health measure that plays a crucial role in preventing the spread of infectious diseases, particularly in communal settings such as schools. The COVID-19 pandemic heightened awareness of hygiene practices, emphasizing the need for sustained interventions to ensure long-term adherence and improved health outcomes among students. This research aims to examine the key factors that shaped students’ hygiene behaviors during the COVID-19 pandemic and evaluate strategies for reinforcing and sustaining these practices over time.MethodsThis study utilized a cross-sectional design to evaluate hand hygiene practices and influencing factors among 3,980 students from grades 5, 9, and 11 in the Karaganda region of Kazakhstan during the COVID-19 pandemic. Data were analyzed using IBM SPSS Statistics 26.0, with Chi-square tests assessing group differences and binary logistic regression identifying factors associated with students’ handwashing behaviors.ResultsThe results revealed that several factors, including school discussions on handwashing, school type (urban vs. rural), gender, grade level, and parental occupation and education, were significantly associated with improved handwashing behavior among students. Urban students, females, higher-grade students, and those with highly educated or employed parents demonstrated better hand hygiene practices, with school-based discussions on handwashing increasing the odds by 38%.ConclusionThis study underscores the critical role of educational interventions, sociodemographic factors, and infrastructure in shaping students’ hand hygiene behaviors, emphasizing the need for sustained efforts to reinforce proper handwashing practices through school-based education, policy support, and improved hygiene facilities.